2004
DOI: 10.1074/jbc.m407086200
|View full text |Cite
|
Sign up to set email alerts
|

Building the Stator of the Yeast Vacuolar-ATPase

Abstract: The vacuolar (H ؉ )-ATPase (or V-ATPase) is a membrane protein complex that is structurally related to F 1 and F 0 ATP synthases. The V-ATPase is composed of an integral domain (V 0 ) and a peripheral domain (V 1 ) connected by a central stalk and up to three peripheral stalks. The number of peripheral stalks and the proteins that comprise them remain controversial. We have expressed subunits E and G in Escherichia coli as maltose binding protein fusion proteins and detected a specific interaction between thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…The E and G subunits have been shown to form stable heterodimers in vitro when co-expressed in E. coli from a bicistronic vector (32). In the current study, we used a similar approach to generate heterodimeric EG complex.…”
Section: Resultsmentioning
confidence: 99%
“…The E and G subunits have been shown to form stable heterodimers in vitro when co-expressed in E. coli from a bicistronic vector (32). In the current study, we used a similar approach to generate heterodimeric EG complex.…”
Section: Resultsmentioning
confidence: 99%
“…Conclusion-Given the available evidence from electron microscopy (8 -10, 19), chemical cross-linking (12,13), and protein biochemistry (11,14), it is likely that the E and G subunits, as a heterodimer, bind at the periphery of the three B subunits to form the peripheral stalks or stators of the V-ATPase enzyme. Furthermore, it has been shown that the E and G subunits connect the V 1 -ATPase domain to the membrane-bound domain of the a subunit as well as the V-ATPasespecific stalk subunits C and H (12, 13, 40 -43).…”
Section: Analysis Of the E And G Subunit Copy Number Usingmentioning
confidence: 99%
“…There is evidence that these elongated proteins densities are formed by the E and G subunits. First, it has been shown that these two subunits are able to form an elongated, heterodimeric complex with equimolar stoichiometry (11), and second, chemical cross-linking from cysteines on the surface of the B subunits indicates close proximity to both E and G subunits from residues distributed between the bottom of the V 1 and the very top (12,13). Recently, Kane and co-workers (14) have shown that there are at least two E and two G subunits per V 1 -ATPase complex.…”
mentioning
confidence: 99%
“…Instability of subunit E-S78A could have occurred if the mutation disrupted interactions between subunits E and G. Early association between subunits E and G is strong and essential for biosynthetic assembly of V 1 V o and V 1 complexes in yeast (58), and in the absence of subunit G (vma10⌬ cells), subunit E is degraded (71). Dimer formation between subunits E and G has been shown (33), and it may be equivalent to the b-b dimer of the F 1 F 0 from Escherichia coli (72), where each individual subunit is essential for assembly of F 1 (73) and has a specialized function within the peripheral stalk (74). Functional parallels may exist between Ala-79 of the b dimer of E. coli and the residues Tyr-46 and Ser-78 of the yeast V-ATPase subunits G and E, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…By making contact with all components of the peripheral stalk(s), subunit E (and possibly G) may represent the foundation for the peripheral stalk(s) (17,28,29). Subunits E and G assemble into E-G dimers (33), and two E-G dimers, associated each with a B subunit, could represent the two peripheral masses detected by two-dimensional electron microscopy of the yeast V 1 complex (34).…”
Section: Vacuolar Hmentioning
confidence: 99%